Acute exacerbation of staphylococcal catarrhal infiltration associated with treatment for Pseudomonas aeruginosa keratitis: A case report. Issue 22 (June 2018) - Bang, Seung Pil; Jun, Jong Hwa
Abstract: Rationale: Simultaneous presentation of peripheral infiltrates, which can be easily misidentified as satellite lesions, is rarely observed in patients with acute infectious keratitis. Patient concerns: A 70-year-old woman was referred to our clinic due to acute mucopurulent keratitis following application of a therapeutic soft contact lens for the treatment of epithelial defects caused by entrance of soil foreign bodies into the eye. The patient was diagnosed with Pseudomonas keratitis, following which she was treated with alternating administration of fourth-generation fluoroquinolone (Vigamox) and 5% fortified ceftazidime eyedrops every 2 hours. Although infectious keratitis rapidly improved, discrete catarrhal infiltrates at the corneolimbal junction (10- to 2-o'clock and 7- to 8-o'clock positions) were rapidly aggravated, forming bead-like stromal pustules inversely proportional to the extent of Pseudomonas keratitis. Diagnosis: Acute exacerbation of staphylococcal catarrhal infiltration associated with treatment for Pseudomonas aeruginosa keratitis. Interventions: Addition of 1% prednisone acetate eyedrops (Pred Forte) four times per day. Outcomes: Dramatic improvement was observed at the sites of catarrhal infiltration without recurrence of infectious keratitis. Lessons: Clinicians should thus remain aware of the risk for co-occurring non-infectious, immune-related keratitis, as treatment for infectious keratitis may induce significant aggravation of non-infectious keratitis.